Frequency and susceptibility pattern of metallo-beta-lactamase producers in a hospital in Pakistan - Fatima Kaleem; Javaid Usman; Afreenish Hassan; Aslam Khan (Journal of Infection in Developing Countries)
Introduction: The rapid spread of acquired metallo-beta-lactamases (MBLs) among major Gram-negative pathogens is an emerging threat and a matter of particular concern worldwide.